2011
DOI: 10.1614/ipsm-d-10-00061.1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Two Biological Control Agents and an Herbicide for Canada Thistle (Cirsium arvense) Suppression

Abstract: We investigated the single and combined effects of two biological control agents, the stem-mining weevilHadroplontus lituraand the pathogenPseudomonas syringaepv.tagetis, with a herbicide (reduced or full application of glyphosate: 0.63 kg ae ha−1, or 3.78 kg ae ha−1, respectively) on the growth of Canada thistle,Cirsium arvense. We hypothesized that first, although each control method would have a negative effect on Canada thistle shoot biomass, root biomass, and shoot number, the integration of more than one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
2
9
1
Order By: Relevance
“…When combining growth environment and parasite control method in the analysis, indoor plants with experimentally added parasites were more negatively affected by dual parasites than outdoor plants. This was unexpected, as outdoor plants are more exposed to suboptimal environmental conditions and stress, which may minimize resources available for compensatory responses (Sciegienka, Keren & Menalled ). A possible explanation could be that the effective parasite load on plants in manipulated indoor experiments is higher than in less controlled outdoor experiments, where parasites are also exposed to naturally occurring predators and parasitoids.…”
Section: Discussionmentioning
confidence: 99%
“…When combining growth environment and parasite control method in the analysis, indoor plants with experimentally added parasites were more negatively affected by dual parasites than outdoor plants. This was unexpected, as outdoor plants are more exposed to suboptimal environmental conditions and stress, which may minimize resources available for compensatory responses (Sciegienka, Keren & Menalled ). A possible explanation could be that the effective parasite load on plants in manipulated indoor experiments is higher than in less controlled outdoor experiments, where parasites are also exposed to naturally occurring predators and parasitoids.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those reported by Ferrero-Serrano et al (2008), who found no effect of weevils on Canada thistle shoot biomass in greenhouse experiments. Conversely, Sciegienka et al (2011) reported that H. litura herbivory negatively impacted Canada thistle shoot biomass, and Collier et al (2007) found inconsistent negative effects. Canada thistle plants grown with common sunflower neighbors or in reduced-nutrient soil produced 64 and 74% less main stem shoot biomass, respectively (Table 1; Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Although these practices can be effective, they are management intensive and often costly (Graglia et al 2006). Although individual management tactics such as herbicides and mechanical methods have been moderately successful (Liu et al 2000), these tactics often do not provide long-term results (Evans 1984;Travnicek et al 2005), and therefore can be prohibitively expensive (Sciegienka et al 2011;Tichich and Doll 2006). Overall, results from previous research suggest that integrated pest management (IPM) may provide longer-lasting Canada thistle suppression when compared to relying on a single chemical or mechanical control tactic (Ferrero-Serrano et al 2008;Sciegienka et al 2011).…”
mentioning
confidence: 99%
“…9 Overall, most scientific literature indicates that these weevils have a minor impact on reducing the spread or distribution of nonstressed thistle populations. 6 Therefore, current research is focusing on integrating this weevil species with other management tactics, such as herbicides, pathogens, and/or plant competition 10,11 The Conflict…”
Section: Home On the Range: Establishment Of A Canada Thistle Biocontmentioning
confidence: 99%